Assessment of background ionizing radiation dose levels in quarry sites located in Ebonyi State, Nigeria - E.O. Echeweozo; F.O. Ugbede (Journal of Applied Sciences and Environmental Management, 2020)
The study presents a radiometric survey of Background Ionizing Radiation (BIR) dose levels in ten quarry sites located in Ebonyi State, Nigeria. In-situ BIR dose rate measurements, by means of nuclear radiation survey meter, at 1 m above ground level were carried out at the excavation section (ES) and quarrying section (QS) of the investigated quarry sites. The obtained results indicated dose rates ranging from from 0.14 to 0.18 μSv/h with mean of 0.15±0.01 μSv/h at the ES and 0.16 to 0.19 μSv/h with mean value of 0.18±0.01 μSv/h at the QS. While the values obtained at the QS are respectively higher than those measured at the ES, they are all higher than the worldwide average value of 84 nSv/h signifying BIR elevated environments. The estimated mean annual effective dose (AED) and excess lifetime cancer risk (ELCR) are 0.27±0.03 mSv/y and 0.94×10–3 respectively at the ES and 0.31±0.02 mSv/y and 1.07×10–3 at the QS. The obtained AED values for all the sites are well above the outdoor worldwide average value of 0.07 mSv/y but lower than the International Commission on Radiological Protection recommended permissible limits of 1.0 mSv/y for the general public. Generally, the BIR levels of the quarry sites are within acceptable limits and no immediate radiological health threat may be derived from the current levels. However, long-term health effects due to continuous exposure to low-level radiation doses may manifested in future over a lifetime exposure of 70 years as indicated by the ELCR values.